Sodium MR Imaging of Articular Cartilage Pathologies - Zbýň, Štefan (Springer US, 2014)
Many studies have proved that noninvasive sodium MR imaging can directly determine the cartilage GAG content, which plays a central role in cartilage homeostasis. New technical developments in the recent decade have helped to transfer this method from in vitro to pre-clinical in vivo studies. Sodium imaging has already been applied for the evaluation of cartilage and repair tissue in patients after various cartilage repair surgery techniques and in patients with osteoarthritis. These studies showed that this technique could be helpful not only for assessment of the cartilage status, but also predictive for osteoarthritis. However, due to the low detectable sodium MR signal in cartilage, sodium imaging is still challenging, and further hardware and software improvements are necessary for translating sodium MR imaging into clinical practice, preferably to 3T MR systems.